Wear-resistant polylactic acid fabric and production process thereof

By using the combination of modified cellulose nanofiber filaments and polycaprolactone segments in polylactic fibers, a three-dimensional network structure is formed and blended with nylon, the problem of poor wear resistance of polylactic fibers is solved and the fibers is improved Wear resistance and mechanical properties enhance the overall performance of the fabric.

CN119308036APending Publication Date: 2025-01-14吉祥三宝高科新材料有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411439687.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Polylactic fibers and their textile products have problems such as poor wear resistance, easy hydrolysis and low heat resistance, which limits their application scope and development prospects.

Method used

Modified cellulose nanofiber filaments are used to graft polycaprolactone segments on their surface and blend with polylactic acid to form a three-dimensional network structure to improve the wear resistance and mechanical properties of the fibers, and can be combined with nylon. Blend to further enhance wear resistance.

Benefits of technology

It significantly improves the wear resistance and mechanical properties of polylactic fibers, reduces the phenomenon of broken heads and thermal decomposition, maintains the biodegradable properties of the material, and enhances the feel and flexibility of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005086024310000091
    Figure BDA0005086024310000091
  • Figure BDA0005086024310000101
    Figure BDA0005086024310000101
Patent Text Reader

Abstract

The invention discloses a wear-resistant polylactic acid fabric, and belongs to the technical field of polylactic acid fabrics, the wear-resistant polylactic acid fabric comprises the following raw materials: 100 parts of polylactic acid, 2-5 parts of modified cellulose nanofibrils and 0.1-1 part of an antioxidant; wherein the surface of the modified cellulose nanofibril is grafted with a polycaprolactone chain segment. The cellulose nanofibrils and the polylactic acid can form a three-dimensional network structure, a good structure supporting effect is achieved, the crystallization property of the polylactic acid can be improved, after grafting modification of the polycaprolactone, the dispersity of the cellulose nanofibrils and the compatibility between the cellulose nanofibrils and the polylactic acid can be improved, and the cellulose nanofibrils and the polylactic acid can be further improved. And the thermal stability of the material can be improved, so that the wear resistance of the polylactic acid fiber and the fabric thereof is improved, and the biodegradable performance of the polylactic acid fiber is not influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polylactic acid fabrics, and in particular relates to wear-resistant polylactic acid fabrics and a production process thereof. Background Art

[0002] Textiles are necessities of human life, with huge consumption and difficult recycling, which have a great impact on the environment. Therefore, vigorously developing new biodegradable textile materials has become one of the current trends in textile technology development. Among them, polylactic acid fiber, as a new biodegradable fiber material, has attracted widespread attention in the textile material industry.

[0003] Polylactic acid fiber combines the performance characteristics of natural fiber and synthetic fiber. It is biodegradable and has good resilience, hydrophilicity and low refractive index, which makes the fabric woven from polylactic acid fiber have drape, soft hand feel, smooth skin touch and excellent gloss. However, polylactic acid fiber and its textile products have problems such as easy hydrolysis, low heat resistance and poor wear resistance, which seriously limit the application scope and development prospects of polylactic acid fabrics. Summary of the invention

[0004] The object of the present invention is to provide a wear-resistant polylactic acid fabric and a production process thereof, so as to solve the problem that polylactic acid fibers and the fabric thereof have poor wear resistance.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a wear-resistant polylactic acid fabric, the raw materials of which include 100 parts of polylactic acid, 2 to 5 parts of modified cellulose nanofibrils and 0.1 to 1 part of an antioxidant; the surface of the modified cellulose nanofibrils is grafted with polycaprolactone segments.

[0007] Preferably, the antioxidant includes a combination of one or more of antioxidant 1010 , antioxidant 1076 , antioxidant BHT, antioxidant 168 and antioxidant 136 .

[0008] The poor wear resistance of polylactic acid fiber not only causes the woven fabric to be prone to pilling, but also causes fiber breakage due to friction between fibers and between fibers and equipment during the production process, thereby affecting the mechanical properties of polylactic acid fiber and its fabric. By adopting the above technical solution, in order to improve the wear resistance of polylactic acid fiber, modified cellulose nanofibrils are also added to the polylactic acid fiber raw material.

[0009] First, cellulose nanofibrils have high elastic modulus and rigidity, which can enhance the mechanical strength of polylactic acid fibers. At the same time, cellulose nanofibrils are also a kind of biomass material, which will not affect the biodegradability of polylactic acid fibers, and the obtained polylactic acid fabrics are still green and environmentally friendly; secondly, the nanoscale and self-properties of modified cellulose nanofibrils make them contain a large number of active groups and show high binding activity. In the process of polylactic acid blending and melting, they will form a spatial mesh interwoven structure inside the system due to the surface hydrogen bonding and the formation of covalent bonds with the polar groups on the polylactic acid molecular chain, thus playing a good supporting structure role in the polylactic acid fiber, which can significantly improve the wear resistance and mechanical properties of polylactic acid fibers and reduce the possible breakage phenomenon in the production process. In addition, nanoscale cellulose fibrils can be used as nucleating agents to improve the crystallization properties of polylactic acid and reduce the generation of defects, thereby improving the thermal stability of polylactic acid fibers and reducing the occurrence of high-temperature thermal degradation.

[0010] However, the large amount of hydroxyl groups on the surface of cellulose nanofibrils leads to the formation of hydrogen bonds between the molecules themselves, and then agglomerates are formed inside the polylactic acid material, which not only hinders the flow of the polylactic acid molecular chain and restricts the polylactic acid crystallization process, but also affects the mechanical properties of the polylactic acid fiber, and does not achieve the corresponding wear resistance improvement effect. Therefore, in order to improve the dispersibility of cellulose nanofibrils in polylactic acid, polycaprolactone segments are grafted on its surface. There is good compatibility between the polycaprolactone segments and polylactic acid, which can improve the compatibility between cellulose nanofibrils and polylactic acid molecular chains. The introduction of polycaprolactone segments also makes the cellulose nanofibrils repel each other, improves their dispersibility in polylactic acid, and further improves the wear resistance and mechanical properties of the obtained polylactic acid fiber. At the same time, after grafting polycaprolactone, not only the thermal stability of the polylactic acid matrix can be improved, but also the thermal stability of the cellulose nanofibrils can be improved, the processing performance of the material can be improved, and the possible breakage and thermal decomposition phenomena in the production process can be reduced.

[0011] Preferably, the raw material of the modified cellulose nanofibrils comprises cellulose nanofibrils and ε-caprolactone in a mass ratio of 1:(9-13).

[0012] More preferably, the diameter of the cellulose nanofibrils is 3 to 5 nm.

[0013] Preferably, the surface of the modified cellulose nanofibrils is also grafted with polyethylene glycol segments; the molecular weight of the polyethylene glycol segments is 1000-2000.

[0014] More preferably, the raw materials of the modified cellulose nanofibrils include cellulose nanofibrils and polyethylene glycol in a mass ratio of 1:(4-8).

[0015] By adopting the above technical solution, the hydroxyl groups on the surface of cellulose nanofibrils can initiate the ring-opening polymerization of ε-caprolactone and then graft copolymerize on the surface of cellulose nanofibrils to obtain polycaprolactone segments, thereby improving the dispersibility and thermal stability of cellulose nanofibrils and enhancing the wear resistance of polylactic acid fibers. Furthermore, since cellulose nanofibrils have high rigidity, the composite with polylactic acid, which has high brittleness, will affect the flexibility and fabric feel of polylactic acid fibers, so the surface of the modified cellulose nanofibrils of the present invention is also grafted with polyethylene glycol segments.

[0016] The polycaprolactone grafted on the surface of cellulose nanofibers is a flexible polymer, which can form a toughening network in cooperation with the polyethylene glycol segments, thereby improving the flexibility of the polylactic acid fiber and the feel of its fabric. At the same time, the formation of a three-dimensional network is conducive to enhancing the structural support of cellulose nanofibers for polylactic acid and improving the wear resistance of polylactic acid fibers and their fabrics. In addition, both polyethylene glycol and polycaprolactone are biodegradable materials and will not affect the biodegradability of polylactic acid fibers.

[0017] Preferably, the modified cellulose nanofibrils are prepared according to the following method: cellulose nanofibrils are mixed with ε-caprolactone and dispersed evenly; the temperature is increased to 120-150°C under a nitrogen atmosphere, a metal catalyst is added, and the reaction is stirred for 4-8 hours, then the temperature is lowered to 80-90°C, polyethylene glycol and the metal catalyst are added, and the reaction is continued to be stirred for 4-5 hours, and finally the modified cellulose nanofibrils are obtained by filtering, washing, centrifuging and drying.

[0018] Preferably, the metal catalyst includes a combination of one or more of stannous octoate, dibutyltin dilaurate, tetrabutyl titanate and tetraisopropyl titanate.

[0019] Preferably, the total amount of the metal catalyst added is 1-2% of the mass of the cellulose nanofibrils.

[0020] By adopting the above technical scheme, cellulose nanofibrils are first grafted with ε-caprolactone to successfully graft polycaprolactone segments on the surface, and at the same time, carboxyl groups are introduced on the surface. Further, under the action of a catalyst, the hydroxyl groups of the polyethylene glycol segments react to achieve the grafting of the polyethylene glycol segments. Finally, the surface of the modified cellulose nanofibrils is grafted with polycaprolactone segments and polyethylene glycol segments at the same time. While improving the dispersibility of the cellulose nanofibrils, the rigidity and thermal stability of the material are coordinated.

[0021] In a second aspect, the present invention provides a production process for wear-resistant polylactic acid fabric, comprising the following process steps:

[0022] S1. Mixing polylactic acid, modified cellulose nanofibrils and an antioxidant in corresponding parts by mass to obtain a polylactic acid premix;

[0023] S2. The obtained polylactic acid premix is ​​melted, spun, wound, stretched and heat-set to obtain polylactic acid fibers;

[0024] S3. The polylactic acid fibers are spun, warped and weaved to obtain wear-resistant polylactic acid fabrics.

[0025] Preferably, the process parameters in step S2 include: melting temperature of 150-190°C, spinning temperature of 200-210°C, winding speed of 1200-2000r / min, drawing temperature of 90-120°C, drawing multiple of 2-3, and heat setting temperature of 100-110°C.

[0026] By adopting the above technical scheme, polylactic acid and modified cellulose nanofibrils are melt-blended and spun, and by adjusting the process parameters during the spinning process, wear-resistant polylactic acid fibers and fabrics thereof are obtained. The problem of broken ends in the production process can also be reduced, the production process can be accelerated, the production efficiency can be improved, and the production quality can be enhanced.

[0027] Preferably, in step S3, the polylactic acid fiber is blended with nylon during the spinning process.

[0028] Preferably, the blending ratio of polylactic acid fiber to nylon is (70-85):(15-30).

[0029] By adopting the above technical solution, in order to further improve the wear resistance of polylactic acid fabrics, polylactic acid fibers can also be blended with nylon. Nylon itself has strong wear resistance and excellent mechanical properties, and can resist deformation when subjected to external forces. After being blended with polylactic acid fibers, the wear resistance and strength of polylactic acid fabrics can be significantly improved.

[0030] Beneficial effects of the present invention:

[0031] 1. The raw materials of the polylactic acid fabric of the present invention include modified cellulose nanofibrils, and the surface of the modified cellulose nanofibrils is grafted with polycaprolactone segments. The cellulose nanofibrils can form a three-dimensional network structure with polylactic acid, play a good supporting structure, and can also improve the crystallization performance of polylactic acid, thereby improving the wear resistance of polylactic acid fiber and its fabric, and the grafted polycaprolactone segments can improve the dispersibility of cellulose nanofibrils and improve the thermal stability of the material. Furthermore, polyethylene glycol segments are grafted on the surface of cellulose nanofibrils, which can form a toughening network in coordination with the polycaprolactone segments, thereby improving the strength and feel of the obtained polylactic acid fiber. In addition, the modified cellulose nanofibers are degradable materials and will not affect the biodegradability of the polylactic acid fiber.

[0032] 2. The polylactic acid fiber of the present invention can also be blended with nylon, and the obtained polylactic acid fabric can have higher wear resistance. DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Preparation Example

[0035] Preparation Example 1: A modified cellulose nanofibril is prepared according to the following method:

[0036] 10 g of cellulose nanofibrils (with a diameter of 3 to 5 nm) were mixed with 110 g of ε-caprolactone and ultrasonically dispersed for 40 minutes to make the dispersion uniform; the temperature was raised to 130°C under a nitrogen atmosphere, 0.1 g of stannous octoate was added, and the reaction was stirred for 7 hours. Finally, the modified cellulose nanofibrils were obtained by filtration, washing, centrifugation and drying.

[0037] Preparation Example 2, a modified cellulose nanofibril, is different from Preparation Example 1 only in that the added amount of ε-caprolactone is 90 g.

[0038] Preparation Example 3, a modified cellulose nanofibril, is different from Preparation Example 1 only in that the added amount of ε-caprolactone is 130 g.

[0039] Preparation Example 4, a modified cellulose nanofibril, is different from Preparation Example 1 only in that the added amount of ε-caprolactone is 80 g.

[0040] Preparation Example 5, a modified cellulose nanofibril, is different from Preparation Example 1 only in that the added amount of ε-caprolactone is 150 g.

[0041] Preparation Example 6: A modified cellulose nanofibril is prepared according to the following method:

[0042] 10 g of cellulose nanofibrils were mixed with 110 g of ε-caprolactone and ultrasonically dispersed for 40 minutes to make the dispersion uniform; the temperature was raised to 130°C under a nitrogen atmosphere, 0.1 g of stannous octoate was added, and the reaction was stirred for 7 hours, then the temperature was lowered to 80°C, 60 g of polyethylene glycol-1500 and 0.1 g of stannous octoate were added, and the reaction was continued to stir for 4 hours. Finally, the modified cellulose nanofibrils were obtained by filtration, washing, centrifugation and drying.

[0043] Preparation Example 7, a modified cellulose nanofibril, is different from Preparation Example 6 only in that an equal amount of polyethylene glycol-600 is used to replace polyethylene glycol-1500.

[0044] Preparation Example 8, a modified cellulose nanofibril, is different from Preparation Example 6 only in that an equal amount of polyethylene glycol-3000 is used to replace polyethylene glycol-1500.

[0045] Preparation Example 9, a modified cellulose nanofibril, prepared according to the following method:

[0046] Under nitrogen atmosphere, 10 g of cellulose nanofibrils and 0.1 g of stannous octoate were added to 60 g of polyethylene glycol-1500, and ultrasonic dispersion was performed for 40 min until uniform dispersion. Then the temperature was raised to 80°C, and the reaction was stirred for 4 h. Finally, the modified cellulose nanofibrils were obtained by filtration, washing, centrifugation and drying.

[0047] Example

[0048] Example 1, a wear-resistant polylactic acid fabric, is prepared according to the following process steps:

[0049] S1. Take 1kg of polylactic acid (density 1.25g / cm 3 ), 40 g of the modified cellulose nanofibrils prepared in Preparation Example 1 and 5 g of an antioxidant (the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1) are uniformly mixed to obtain a polylactic acid premix;

[0050] S2. The obtained polylactic acid premix was melted, spun, wound, stretched and heat-set to obtain polylactic acid fibers, wherein the melting temperature was 180°C, the spinning temperature was 210°C, the winding speed was 1500 r / min, the stretching temperature was 110°C, the stretching ratio was 2.3, and the heat setting temperature was 100°C;

[0051] S3. The polylactic acid fibers are spun, warped and weaved to obtain wear-resistant polylactic acid fabrics.

[0052] Example 2, a wear-resistant polylactic acid fabric, is prepared according to the following process steps:

[0053] S1. Take 1kg of polylactic acid (density 1.25g / cm 3 ), 20 g of the modified cellulose nanofibrils prepared in Preparation Example 3 and 5 g of an antioxidant (the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1) are uniformly mixed to obtain a polylactic acid premix;

[0054] S2. The obtained polylactic acid premix was melted, spun, wound, stretched and heat-set to obtain polylactic acid fibers, wherein the melting temperature was 165°C, the spinning temperature was 200°C, the winding speed was 1200 r / min, the stretching temperature was 90°C, the stretching ratio was 2.3, and the heat setting temperature was 100°C;

[0055] S3. The polylactic acid fibers are spun, warped and weaved to obtain wear-resistant polylactic acid fabrics.

[0056] Example 1, a wear-resistant polylactic acid fabric, is prepared according to the following process steps:

[0057] S1. Take 1kg of polylactic acid (density 1.25g / cm 3 ), 50 g of the modified cellulose nanofibrils prepared in Preparation Example 2 and 5 g of an antioxidant (the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1) are uniformly mixed to obtain a polylactic acid premix;

[0058] S2. The obtained polylactic acid premix was melted, spun, wound, stretched and heat-set to obtain polylactic acid fibers, wherein the melting temperature was 190°C, the spinning temperature was 210°C, the winding speed was 2000 r / min, the stretching temperature was 120°C, the stretching ratio was 2.5, and the heat setting temperature was 110°C;

[0059] S3. The polylactic acid fibers are spun, warped and weaved to obtain wear-resistant polylactic acid fabrics.

[0060] Example 4 is a wear-resistant polylactic acid fabric, which is different from Example 1 only in that the modified cellulose nanofibrils prepared in Preparation Example 1 are replaced by an equal amount of modified cellulose nanofibrils prepared in Preparation Example 4.

[0061] Example 5, a wear-resistant polylactic acid fabric, is different from Example 1 only in that the modified cellulose nanofibrils prepared in Preparation Example 1 are replaced by an equal amount of modified cellulose nanofibrils prepared in Preparation Example 5.

[0062] Example 6, a wear-resistant polylactic acid fabric, is different from Example 1 only in that the modified cellulose nanofibrils prepared in Preparation Example 1 are replaced by an equal amount of modified cellulose nanofibrils prepared in Preparation Example 6.

[0063] Example 7, a wear-resistant polylactic acid fabric, is different from Example 1 only in that the modified cellulose nanofibrils prepared in Preparation Example 1 are replaced by an equal amount of modified cellulose nanofibrils prepared in Preparation Example 7.

[0064] Example 8, a wear-resistant polylactic acid fabric, is different from Example 1 only in that the modified cellulose nanofibrils prepared in Preparation Example 1 are replaced by an equal amount of modified cellulose nanofibrils prepared in Preparation Example 8.

[0065] Example 9, a wear-resistant polylactic acid fabric, differs from Example 1 only in that nylon (FDY nylon filament, denier 40) is blended with polylactic acid fiber in step S3, and then the wear-resistant polylactic acid fabric is obtained through warping and weaving, wherein the blending ratio of polylactic acid fiber to nylon is 70:30.

[0066] Example 10, a wear-resistant polylactic acid fabric, is different from Example 9 only in that the blending ratio of polylactic acid fiber to nylon is 85:15.

[0067] Comparative Example

[0068] Comparative Example 1 is a wear-resistant polylactic acid fabric, which is different from Example 1 only in that the added amount of the modified cellulose nanofibrils prepared in Preparation Example 1 is 10 g.

[0069] Comparative Example 2 is a wear-resistant polylactic acid fabric, which is different from Example 1 only in that the added amount of the modified cellulose nanofibrils prepared in Preparation Example 1 is 70 g.

[0070] Comparative Example 3 is a wear-resistant polylactic acid fabric, which is different from Example 1 only in that the modified cellulose nanofibrils prepared in Preparation Example 1 are replaced by an equal amount of modified cellulose nanofibrils prepared in Preparation Example 9.

[0071] Comparative Example 4 is a wear-resistant polylactic acid fabric, which is different from Example 1 only in that the modified cellulose nanofibrils prepared in Preparation Example 1 are replaced by an equal amount of unmodified cellulose nanofibrils.

[0072] Comparative Example 5 is a wear-resistant polylactic acid fabric, which is different from Example 1 only in that the modified cellulose nanofibrils prepared in Preparation Example 1 are not added.

[0073] Performance testing

[0074] 1. Performance test of polylactic acid fiber: According to the relevant records in GB / T 3916-2013 "Determination of breaking strength and breaking elongation of single yarn of textile package yarn (CRE method)", the tensile properties of polylactic acid fibers in the examples and comparative examples were tested, wherein the clamping length was 500 mm and the stretching speed was 500 mm / min.

[0075] The test results are shown in Table 1.

[0076] 2. Polylactic acid fabric performance test:

[0077] (1) Wear resistance test: According to the relevant records in GB / T 21196.3-2007 "Determination of the abrasion resistance of textile fabrics by the Martindale method - Part 3: Determination of mass loss", the wear resistance of the polylactic acid fabrics obtained in the examples and comparative examples was tested to obtain the wear rate.

[0078] (2) Strength test: According to the relevant records in GB / T 19976-2005 “Determination of bursting strength of textiles - Steel ball method”, the strength of the polylactic acid fabrics obtained in the examples and comparative examples was tested.

[0079] The test results are shown in Table 2.

[0080] Table 1 Test results of tensile properties of polylactic acid fibers

[0081]

[0082] Table 2. Test results of polylactic acid fabric performance

[0083]

[0084] According to Table 1 and Table 2, in combination with Example 1, Example 2 and Example 3, it can be seen that the tensile properties of the polylactic acid fiber and the wear resistance and strength of the polylactic acid fabric in Example 2 and Example 3 are not much different from those in Example 1. Compared with Example 1, Example 2 and Example 3 only change the raw materials and the raw material ratio within the required range, which has little effect on the performance of the material.

[0085] Combining Example 1, Example 4 and Example 5, it can be seen that the tensile properties of the polylactic acid fiber in Example 4 and Example 5 are reduced compared with Example 1, and the wear resistance and strength of the polylactic acid fabric are reduced. The changes between Example 4 and Example 5 compared with Example 1 are that the content of the polycaprolactone segment grafted on the surface of the modified cellulose nanofibrils is different. Specifically, the amount of polycaprolactone monomer added in Example 4 is reduced, resulting in a short polycaprolactone segment formed, and the effect of improving the dispersibility and thermal stability is not obvious. The amount of polycaprolactone monomer added in Example 5 is increased, which will affect the formation of a three-dimensional space bracket structure between the cellulose nanofibrils and the polylactic acid, thereby affecting the wear resistance of the material.

[0086] Combining Example 1, Example 6 to Example 8, it can be seen that the tensile properties of the polylactic acid fiber in Example 6 are improved compared with that in Example 1, especially the elongation at break is increased, and the wear resistance and strength are slightly enhanced. Compared with Example 1, the surface of the modified cellulose nanofibrils used in Example 6 is also grafted with polyethylene glycol segments, which can synergistically form a toughening network with polycaprolactone, improve the flexibility of the material, improve the tensile properties, and will not affect the reinforcing effect of cellulose nanofibrils on polylactic acid fibers. Compared with Example 6, the performance of Examples 7 and 8 is reduced. The molecular weight of the polyethylene glycol used in Example 7 is too small, and the effect of the reaction link with polycaprolactone is small, and the toughening effect is reduced; the molecular weight of the polyethylene glycol in Example 8 is too large, which will introduce a large number of additional hydroxyl groups, which is not conducive to the dispersion of the modified cellulose nanofibrils, thereby affecting the material properties.

[0087] Combining Example 1, Example 9 and Example 10, it can be seen that the wear resistance of the polylactic acid fabrics in Examples 9 and 10 is enhanced compared to that in Example 1, indicating that the use of nylon blending in the weaving process of the polylactic acid fabric can enhance the wear resistance of the material to a certain extent.

[0088] Combining Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 5, it can be seen that the tensile properties of the polylactic acid fiber of Comparative Example 1, Comparative Example 2 and Comparative Example 5 are significantly reduced compared with those of Example 1, and the wear resistance and strength of the polylactic acid fabric are significantly reduced, among which the reduction in Comparative Example 5 is more significant. Compared with Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 5 change the amount of modified cellulose nanofibrils added. Specifically, the amount of addition is reduced in Comparative Example 1, which will lead to a weakened reinforcing effect on the polylactic acid fiber, and it is difficult to form a spatial network structure and support the polylactic acid fiber structure. It is easy to break during the production process, affecting the fiber and its fabric performance. In Comparative Example 5, no modified cellulose nanofibrils are added, and the performance decline is more obvious. In Comparative Example 2, the amount of modified cellulose nanofibrils added is increased, and excessive addition will still cause the modified cellulose nanofibrils to flocculate in the system, thereby destroying the orderliness of the molecular arrangement of the polylactic acid matrix, seriously affecting the improvement of the thermal stability of the material, and is not conducive to the performance enhancement of the material.

[0089] Combining Example 1, Comparative Example 3 and Comparative Example 4, it can be seen that the tensile properties of the polylactic acid fibers of Comparative Example 3 and Comparative Example 4 are significantly reduced compared to those of Example 1, and the wear resistance and strength of the polylactic acid fabric are significantly reduced. The modified cellulose nanofibrils used in Comparative Example 3 are only grafted with polyethylene glycol segments on the surface. Although the dispersibility of the modified cellulose nanofibrils can be improved to a certain extent, the lack of polycaprolactone segments reduces the thermal stability of the material, and the compatibility with the polylactic acid matrix is ​​also reduced, which is not conducive to the improvement of the wear resistance and strength of the material. The cellulose nanofibrils used in Comparative Example 4 have not been modified, and are easy to agglomerate themselves during the polylactic acid blending process, which will hinder the movement of the polylactic acid molecular chain, affect the crystallization process of the polylactic acid, and increase the internal defect content of the material, which is not conducive to the improvement of the wear resistance and strength of the polylactic acid fabric.

[0090] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0091] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A wear-resistant polylactic acid fabric, characterized in that: The raw materials of the wear-resistant polylactic acid fabric include 100 parts of polylactic acid, 2 to 5 parts of modified cellulose nanofibrils and 0.1 to 1 part of antioxidant; the surface of the modified cellulose nanofibrils is grafted with polycaprolactone chain segments.

2. The wear-resistant polylactic acid fabric according to claim 1, characterized in that: The raw materials of the modified cellulose nanofibrils include cellulose nanofibrils and ε-caprolactone in a mass ratio of 1:(9-13).

3. The wear-resistant polylactic acid fabric according to claim 1, characterized in that: The surface of the modified cellulose nanofibrils is also grafted with polyethylene glycol segments; the molecular weight of the polyethylene glycol segments is 1000-2000.

4. The wear-resistant polylactic acid fabric according to claim 3, characterized in that: The modified cellulose nanofibrils are prepared according to the following method: cellulose nanofibrils and ε-caprolactone are mixed and dispersed uniformly; the temperature is increased to 120-150° C. under a nitrogen atmosphere, a metal catalyst is added, and the reaction is stirred for 4-8 hours, then the temperature is lowered to 80-90° C., polyethylene glycol and the metal catalyst are added, and the reaction is continued to be stirred for 4-5 hours, and finally the modified cellulose nanofibrils are obtained by filtering, washing, centrifuging and drying.

5. The wear-resistant polylactic acid fabric according to claim 4, characterized in that: The metal catalyst includes a combination of one or more of stannous octoate, dibutyltin dilaurate, tetrabutyl titanate and tetraisopropyl titanate.

6. The wear-resistant polylactic acid fabric according to claim 1, characterized in that: The antioxidant includes one or more of antioxidant 1010 , antioxidant 1076 , antioxidant BHT, antioxidant 168 and antioxidant 136 .

7. A production process for wear-resistant polylactic acid fabric according to any one of claims 1 to 6, characterized in that: The process steps include: S1. Mixing polylactic acid, modified cellulose nanofibrils and an antioxidant in corresponding parts by mass to obtain a polylactic acid premix; S2. The obtained polylactic acid premix is ​​melted, spun, wound, stretched and heat-set to obtain polylactic acid fibers; S3. The polylactic acid fibers are spun, warped and weaved to obtain wear-resistant polylactic acid fabrics.

8. The production process of wear-resistant polylactic acid fabric according to claim 7, characterized in that: In the step S3, the polylactic acid fiber is blended with nylon during the spinning process.

9. The production process of wear-resistant polylactic acid fabric according to claim 8, characterized in that: The blending ratio of the polylactic acid fiber to nylon is (70-85):(15-30).

10. The production process of wear-resistant polylactic acid fabric according to claim 7, characterized in that: The process parameters in step S2 include: melting temperature of 150-190°C, spinning temperature of 200-210°C, winding speed of 1200-2000r / min, drawing temperature of 90-120°C, drawing multiple of 2-3, and heat setting temperature of 100-110°C.

Citation Information

Cited By

  • Modified polylactic acid high-temperature-resistant degradable composite material and preparation method thereof

    CN121086490A

  • Short-process dyeing and finishing process for polyester-cotton school uniform fabric

    CN121381411A